1989
DOI: 10.1177/004051758905900606
|View full text |Cite
|
Sign up to set email alerts
|

Photolytic Properties of Ortho-Substituted 4-[N,N-Bis(β- Hydroxyethyl)amino]azobenzenes in Polymer Substrates

Abstract: The synthesis of some novel derivatives of 4-[ N,N -bis(β-hydroxyethyl)-amino]azobenzene is reported, and the effects of ortho -substituents on photoinduced trans → cis isomerism about the azo group, mass spectral behavior, and the photostability of these dyes are described. An ortho-nitro group inhibits trans → cis photoisomerism about the azo group and affords poor photostability. Those ortho-substituted dyes showing a greater tendency to undergo photoinduced trans → cis isomerism and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The light fading phenomena of dyes and dyed substrates have been studied focusing on the fading mechanisms of dyes [8e10]. There are several reports on photochemical dealkylation of amino groups of dyes [11,12], although an example with a benzyl group is still unknown. A benzyl group is also well-known as a protecting group for amino moieties in addition to that for alcoholic hydroxy groups [13].…”
Section: Introductionmentioning
confidence: 99%
“…The light fading phenomena of dyes and dyed substrates have been studied focusing on the fading mechanisms of dyes [8e10]. There are several reports on photochemical dealkylation of amino groups of dyes [11,12], although an example with a benzyl group is still unknown. A benzyl group is also well-known as a protecting group for amino moieties in addition to that for alcoholic hydroxy groups [13].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the model yellow GAD (4) has been accomplished according to the previously described (Bianchini et al 2008) procedure showed in Fig 1, starting from known compounds 1 ( Bartalucci et al 2007) and 2 (Freeman & McIntosh 1989). A solution of compound 1 (0.97 g, 3.40 mmol) (Fig 1) and compound 2 (2.40 g, 6.66 mmol) in dry tetrahydrofuran (THF) (20 mL) was treated at room temperature with 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC, 1.28 g, 6.68 mmol) and 4-dimethylaminopyridine (DAMP, 244 mg, 2.00 mmol) and the solution was stirred at room temperature until the starting material completely disappeared (thin layer chromatography e TLC, 12 h).…”
Section: Chemical Synthesis Of 4-{nn-bis[2-(d-galactopyranos-6-yloxymentioning
confidence: 99%
“…To our knowledge, it was the first report on the debenzylation of amino groups in organic dyes, whereas there are several reports on the corresponding N-dealkylation reaction [25][26][27].…”
Section: Introductionmentioning
confidence: 99%